Selective CO2 hydrogenation to formic acid with multifunctional ionic liquids - Weilhard, Andreas; Qadir, Muhammad Irfan; Sans, Victor; Dupont, Jairton (American Chemical Society, 2018)
The development of simple, cost-effective and sustainable methods to transform CO2 into feedstock chemicals is essential to reduce the dependence on fossil fuels of the chemical industry. Here, we report the selective and efficient catalytic hydrogenation of CO2 to formic acid (FA) using a synergistic combination of an ionic liquid (IL) with basic anions and relatively simple catalysts derived from the precursor Ru3(CO)12]. Very high values of TON (17000) and TOF have been observed and FA solutions with concentrations of up to 1.2 M have been produced. In this system, the imidazolium based IL associated with the acetate anion acts as precursor for the formation of the catalytically active Ru-H species, catalyst stabilizer and as an acid buffer, shifting the equilibrium towards free formic acid. Moreover, the IL acts as an entropic driver (via augmentation of the number of microstates), lowering the entropic contribution imposed by the IL surrounding the catalytically active sites. The favorable thermodynamic conditions enable the reaction to proceed efficiently at low pressure pressures, and furthermore the immobilization of the IL onto a solid support facilitates the separation of FA at the end of the reaction.